2002
DOI: 10.1021/bi011753g
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Change Coupling the Dimerization and Activation of KSHV Protease

Abstract: The mechanism of herpesviral protease activation upon dimerization was studied using two independent spectroscopic assays augmented by directed mutagenesis. Spectroscopic changes, attributable to dimer interface conformational plasticity, were observed upon dimerization of Kaposi's sarcoma-associated herpesvirus protease (KSHV Pr). KSHV Pr's dissociation constant of 585 +/- 135 nM at 37 degrees C was measured by a concentration-dependent, 100-fold increase in specific activity to a value of 0.275 +/- 0.023 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…Previous studies have shown that herpesvirus proteases are regulated by a dimerization-linked conformational change that disrupts the oxyanion loop necessary for transition state stabilization (18,(32)(33)(34). Dimerization induces the folding of helix 5 and helix 6, which stabilize the oxyanion hole and contribute to the surprisingly weak binding affinity of these proteases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that herpesvirus proteases are regulated by a dimerization-linked conformational change that disrupts the oxyanion loop necessary for transition state stabilization (18,(32)(33)(34). Dimerization induces the folding of helix 5 and helix 6, which stabilize the oxyanion hole and contribute to the surprisingly weak binding affinity of these proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of multiple engineered mutations in the KSHV Pr interfacial helix, adjacent to the active site and in the active site, which result in obligate monomers, has shown that loss of dimerization and activity is not linked to any specific point mutant, such as M197D (18; data not shown). The M197D point mutation has been shown to result in obligate monomers, which are structurally indistinct from wild-type monomers isolated at temperatures which allow dimer dissociation (18). In addition, a monomer containing the M197D substitution as well as a cross-link between helix 6 and the oxyanion loop has proteolytic activity (34).…”
Section: Quantification Of Structural Differences Between the Monomermentioning
confidence: 99%
See 2 more Smart Citations
“…Examples are the use of 25% glycerol for HSV1 protease [21], 0.5 M Na 2 SO 4 and 10% glycerol for CMV [17], 30% sucrose for CMV [22], 0.8 M potassium phosphate and 25% glycerol for KSHV protease [23]. As most of the enzymological studies have been done in the presence of such agents little kinetic data has been determined in their absence.…”
Section: Introductionmentioning
confidence: 99%